Study Literature of PISA-Based Test Instruments on Students’ Mathematical Reasoning Ability (Jurusan Matematika FMIPA UNNES, 2023)
This research was motivated by the lack of students' mathematical reasoning abilities in learning mathematics. Indonesia in the past few years has always been in the bottom 10 ranks in the PISA test, which is proof that the level of students' mathematical reasoning is still low. The use of PISA-based test instruments is still rarely used in the Indonesian education system. This study aims to analyze the PISA-based test instrument on students' mathematical reasoning abilities. This research was structured with a literature study approach, then the data were analyzed descriptively by presenting facts or findings which were then reviewed theoretically. Based on what has been studied, the PISA-based test instrument can develop students' mathematical reasoning abilities. The conclusion of this literature study can be stated that the development of PISA-based test instruments can measure students' mathematical reasoning abilities.